2001
DOI: 10.3758/bf03196189
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing semantic space: Neighborhood effects in word recognition

Abstract: Object-Based SemanticsMany models of semantics have attempted to address the preceding questions. These models can be categorized A specification of the structural characteristicsof the mental lexicon is a central goal in word recognition research. Of various word-level characteristics,semantics remains the most resistant to this endeavor. Although there are several theoretically distinct models of lexical semantics with fairly clear operational definitions (e.g., in terms of feature sharing, category membersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
203
2
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(227 citation statements)
references
References 40 publications
17
203
2
5
Order By: Relevance
“…Consequently, in the text-based adjective analyses, the principle components analyses were based on the correlation matrix of the 88 adjective occurrences across the 1165 participants' essays. Note that the assumptions underlying this approach are congruent with those in latent semantic analysis (Landauer, Foltz, & Laham, 1998), computational modeling of semantic spaces (e.g., Buchanan, Westbury, & Burgess, 2001), and other approaches to explore natural language patterns (e.g., Graesser, Cai, Louwerse, & Daniel, 2006;Graesser, Lu, Jackson, Mitchell, Ventura, Olney, & Louwerse, 2004;Graesser, McNamara, Louwerse, & Cai, 2004). Although we report the results from principal components analyses with varimax rotation, virtually identical results were obtained using principal axis analyses and with promax, oblique, and equamax rotations.…”
Section: Text Analytic Strategymentioning
confidence: 44%
“…Consequently, in the text-based adjective analyses, the principle components analyses were based on the correlation matrix of the 88 adjective occurrences across the 1165 participants' essays. Note that the assumptions underlying this approach are congruent with those in latent semantic analysis (Landauer, Foltz, & Laham, 1998), computational modeling of semantic spaces (e.g., Buchanan, Westbury, & Burgess, 2001), and other approaches to explore natural language patterns (e.g., Graesser, Cai, Louwerse, & Daniel, 2006;Graesser, Lu, Jackson, Mitchell, Ventura, Olney, & Louwerse, 2004;Graesser, McNamara, Louwerse, & Cai, 2004). Although we report the results from principal components analyses with varimax rotation, virtually identical results were obtained using principal axis analyses and with promax, oblique, and equamax rotations.…”
Section: Text Analytic Strategymentioning
confidence: 44%
“…Words with many associates (e.g., movie) can thus be identified as having large semantic neighborhoods, whereas small-neighborhood words are those with relatively few associates (e.g., dog). Previous research has shown that in a lexical decision task, words with large semantic neighborhoods are responded to more rapidly than words with sparse semantic neighborhoods (Buchanan, Westbury, & Burgess, 2001;Locker, Simpson, & Yates, 2003).…”
mentioning
confidence: 99%
“…Behavioral studies that quantified semantic neighborhood according to this model have found that words with large neighborhoods are processed more quickly and accurately than words with small neighborhoods. This facilitatory effect has been found in lexical decision (Buchanan et al, 2001;Pexman et al, 2008;Yap et al, 2012;Yap et al, 2011) and naming tasks (Buchanan et al, 2001). However, the effects in semantic categorization tasks are not consistent.…”
Section: Multidimensionality Of Semantic Richnessmentioning
confidence: 80%
“…Muller et al (2010) and Laszlo & Federmeier (2011) found larger N400 amplitudes in words with high NA than words with low NA. In contrast, Rabovsky et al (2012) Finally, NSN is a dimension that has been investigated in a number of behavioral studies (Buchanan et al, 2001;Pexman et al, 2008;Yap et al, 2012;Yap et al, 2011) and there is evidence that its effects are modulated by task demands Yap et al, 2012;Yap et al, 2011). However, the neural dynamics of NSN have not yet been investigated.…”
Section: Neural Dynamics Associated With Semantic Richnessmentioning
confidence: 99%